2014
DOI: 10.1007/s13760-014-0395-7
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin 8 % as a cutaneous patch (Qutenza™): analgesic effect on patients with peripheral neuropathic pain

Abstract: Evaluation of the analgesic effect after a single application of the capsaicin 8 % cutaneous patch (Qutenza™) in 37 patients suffering from painful, distal symmetric polyneuropathy (PNP) for an average of 5 years. Patients ranged from 40 to 78 years of age and 22 subjects were HIV-positive. Patients were observed 4 weeks prior to 12 weeks post administration. An evaluation of the therapeutic effect of capsaicin 8 % as a dermal patch in terms of pain reduction, change of sleeping behavior and social activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
6
0
4
Order By: Relevance
“…No other side effects were reported, and the treatment-induced erythema did not evoke secondary hyperpigmentation in any of the subjects. The underlying cause of this noticeable difference in treatment response in NP is unknown, but similar response variation has been observed in the treatment of post-herpetic neuralgia 15 . Of interest, as can be seen in Fig.…”
Section: Discussionmentioning
confidence: 77%
“…No other side effects were reported, and the treatment-induced erythema did not evoke secondary hyperpigmentation in any of the subjects. The underlying cause of this noticeable difference in treatment response in NP is unknown, but similar response variation has been observed in the treatment of post-herpetic neuralgia 15 . Of interest, as can be seen in Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Administration of a capsaicin 8% patch has been applied for painful polyneuropathy and post‐herpetic neuralgia therapy (Backonja et al., ; Simpson et al., ; Clifford et al., ; Irving et al., ; Raber et al., ). Plasma concentration of capsaicin declined below the detection limit within 4.5 h after patch application (Babbar et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether nociceptor activation per se is a crucial aspect of this desensitization process. Some clinical studies have asserted that the use of local anesthetics do not reduce the efficacy of the capsaicin-ablation 44,68,83 . Experimental studies have found an association between the pain experienced during patch application and the efficacy of the desensitization…”
Section: Capsaicin Ablationmentioning
confidence: 99%